Seni Decoupage sebagai Sarana Mewujudkan Masyarakat Inklusif - Trisniawati; Wahyu Setya Ratri (Dinamisia : Jurnal Pengabdian Kepada Masyarakat, 2020)
This study aims to describe how decoupage is a means to realize an inclusive society. This is expected to overcome environmental problems especially inorganic waste management through decoupage. This research was conducted in Jatirejo, Lendah, Kulon Progo, Yogyakarta. Data analyzed in the form of primary data, namely questionnaire on the implementation of activities and the results of interviews. The results of the study show that the community can participate in decoupage activities well. In the evaluation of 45 diffable material present in indicator 1. the material can be received clearly as many as 2 disabilities give a score of 1, 2 disables give a score of 2, 20 disabilities give a score of 3, and 21 disabilities give a score of 4. On the indicator 2. the material is useful for 3 difabel participants gave a score of 1, 3 difabel gave a score of 2, 10 difabel gave a score of 3, and 10 difabel gave a score of 4. In indicator 3. material distributed to participants as much as 1 diffable gave a score of 1, 1 difabel gave a score of 2, 18 difabel give a score of 3 and 25 with disabilities give a score of 4.